NILAI-NILAI PENDIDIKAN KARAKTER UNTUK ANAK USIA DINI DALAM FILM â€œNUSSAâ€ - Fardani, Diah Novita; Lismanda, Yorita Febry (Universitas Islam Malang, 2019)
Early Childhood has a variety of interests, one of them is the fondness of watching television shows that are animated cartoons. At an early age, children have a strong tendency to mimic everything they see. This becomes important considering that a lot of animated cartoon films are shown and are often seen by children which certainly affects the character and personality of children.This study aims to determine the values of character education forearly childhood contained in the animated film